Female Authorship, Incomplete Archives, and the Periodical Press in Nineteenth-Century Montreal: The Case of Rosanna Mullins Leprohon - Cabajsky, Andrea (Port Acadie)

(untitled) (Université Sainte-Anne, 2022)
This article revolves around a case study of Montreal-based, Irish-Canadian author Rosanna Mullins Leprohon (1829-1879) who left behind little to no material archive after her death in 1879. Leprohon’s example serves to highlight the scholarly challenges that inhere in defining Canadian women’s authorship in the nineteenth century. The article is divided into two parts: focussing on the Journal of Education for Lower Canada (Montreal, 1857-1879), the first half argues that Leprohon’s periodical poetry played a greater role than previously understood in defining the terms of her authorship in Confederation-period Montreal. Examining archival documents belonging to her late husband and held in the Fonds Jean-Lukin Leprohon, the second half demonstrates the challenges that inhere in reconstructing women’s authorship through the archives of men-of-letters. Although they may never make up for the absence of private correspondence written in her own voice, Rosanna Leprohon’s periodical poems represent valuable resources for reconstructing the terms of her authorship and visibility in Montreal in the middle decades of the nineteenth century.